2012
DOI: 10.1126/science.1225829
|View full text |Cite
|
Sign up to set email alerts
|

A Programmable Dual-RNA–Guided DNA Endonuclease in Adaptive Bacterial Immunity

Abstract: Clustered regularly interspaced short palindromic repeats (CRISPR)/CRISPR-associated (Cas) systems provide bacteria and archaea with adaptive immunity against viruses and plasmids by using CRISPR RNAs (crRNAs) to guide the silencing of invading nucleic acids. We show here that in a subset of these systems, the mature crRNA that is base-paired to trans-activating crRNA (tracrRNA) forms a two-RNA structure that directs the CRISPR-associated protein Cas9 to introduce double-stranded (ds) breaks in target DNA. At … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

161
13,355
10
223

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14,056 publications
(13,749 citation statements)
references
References 47 publications
161
13,355
10
223
Order By: Relevance
“…The creation of specific DNA breaks can be obtained by the expression of nucleases such as zinc‐finger nucleases (ZFNs), transcription activator‐like effector nucleases (TALENs) and, more recently, the Cas9 protein associated with type II clustered regulatory interspaced short palindromic repeats (CRISPR) (Hsu et al ., 2014). CRISPR‐Cas9 relies on the presence of a 20‐nucleotide guide RNA (sgRNA) that targets specifically the Cas9 nuclease to the complementary genomic sequence (Jinek et al ., 2012). The sgRNA harbours the so‐called ‘protospacer adjacent motif’ (PAM), for which the consensus sequence, NGG, is adjacent to the 3′ end of the 20‐bp target.…”
Section: Introductionmentioning
confidence: 99%
“…The creation of specific DNA breaks can be obtained by the expression of nucleases such as zinc‐finger nucleases (ZFNs), transcription activator‐like effector nucleases (TALENs) and, more recently, the Cas9 protein associated with type II clustered regulatory interspaced short palindromic repeats (CRISPR) (Hsu et al ., 2014). CRISPR‐Cas9 relies on the presence of a 20‐nucleotide guide RNA (sgRNA) that targets specifically the Cas9 nuclease to the complementary genomic sequence (Jinek et al ., 2012). The sgRNA harbours the so‐called ‘protospacer adjacent motif’ (PAM), for which the consensus sequence, NGG, is adjacent to the 3′ end of the 20‐bp target.…”
Section: Introductionmentioning
confidence: 99%
“…The HNH nuclease domain of SpCas9 undergoes a substantial conformational rearrangement upon target binding 1215 , which activates the RuvC nuclease for concerted cleavage of both strands of the DNA 12,16 . It was previously shown that the HNH domain stably docks in its active state with an on-target substrate, but becomes loosely trapped in a catalytically-inactive conformational checkpoint when bound to mismatched targets 10,12 .…”
mentioning
confidence: 99%
“…The sgRNA contains both a CRISPR RNA component (crRNA) as well as a trans‐activating crRNA, that binds to Cas9 and directs it to a specific sequence of interest via Watson–Crick base pairing ( Figure 1 ). 56 Multiplexed targeting by endonuclease Cas9 can be achieved at an unprecedented scale by employing a battery of short guide RNAs instead of a library of bulky proteins. The only criterion for defining the target is that it needs to be close to a PAM, DNA sequence, consisting of either NGG or NAG 57.…”
Section: Crispr/cas9mentioning
confidence: 99%